Molecular Analysis of Immune-Escape Mutants of Hepatitis B Virus from Local Clinical Samples - CHANDRA JINATA; ERNAWATI ARIFIN GIRI-RACHMAN; DEBBIE SOEFIE RETNONINGRUM (Microbiology Indonesia, 2012)
Small hepatitis B surface antigen (sHBsAg) is used as a component of hepatitis B vaccine. Even though this vaccine is known to be effective in preventing hepatitis B disease, natural mutation may induce Hepatitis B Virus (HBV) to form immune-escape mutant. This mutant is not only capable of infecting hepatitis B-vaccinated people, but also causing commercial diagnostic assay failure. Immune-escape mutant is generally detected from amino acid change at Major Hydrophilic Region (MHR) of sHBsAg while the change occurred outside the region may also lead to immune-escape mutant formation. This research was aimed to investigate the presence of HBV immune-escape mutants in local clinical samples in Indonesia. sHBsAg gene of seventeen HBV samples from local patients were amplified by polymerase chain reactions then subjected to two-directional sequencing. The DNA sequences later were analyzed by bioinformatics programs. Fifteen out of seventeen samples were genotype B and subtype adw2, while the other two were genotype C and subtype adrq+. Among fifteen genotype B samples, twelve of them were not immune-escape mutants, two were immune-escape mutants that have been previously reported (Gln129Arg and Met133Leu), and one was a mutant outside MHR that has not been previously reported as an immune-escape mutant (Tyr161Ser). Both samples of genotype C group were not immune-escape mutants. As conclusion, by investigating seventeen local clinical HBV samples, it was known that two of seventeen samples were confirmed as immune-escape mutants and one of seventeen samples was a mutant outside MHR.